2016
DOI: 10.1002/ange.201605113
|View full text |Cite
|
Sign up to set email alerts
|

Chemische Verzwilligung von Salz und Metall in den Subnitridometallaten Ba23Na11(MN4)4 mit M=V, Nb, Ta

Abstract: Die Subnitridometallate Ba23Na11(MN4)4 (M=V, Nb, Ta) kristallisieren in einem neuen Strukturtyp, in dem sowohl ionische ortho‐Nitridometallat‐Anionen als auch Strukturmotive aus einfachen (inter)metallischen Packungen zu finden sind: Na‐zentrierte [Na8]‐Würfel als Ausschnitte aus der bcc‐Struktur von elementarem Natrium und Na‐zentrierte [Ba10Na2]‐Ikosaeder, wie sie z. B. in Laves‐Phasen vorkommen. Einkristall‐ und Pulverröntgenstrukturanalyse unterstreichen in Kombination mit quantenchemischen Berechnungen de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Ba 6 [(Mo 1– x Ta x )N 4 ]N 0.86 single crystals were yielded as main product in a synthesis targeted on the formation of the hypothetical subnitridomolybdate “Ba 23 Na 11 (MoN 4 ) 4 ”, analogous to the reported V, Nb, and Ta compounds . NaBa was the only byphase (see powder diffraction pattern in Figure S4, Supporting Information), in accordance with the reaction equation:…”
Section: Methodsmentioning
confidence: 53%
See 2 more Smart Citations
“…Ba 6 [(Mo 1– x Ta x )N 4 ]N 0.86 single crystals were yielded as main product in a synthesis targeted on the formation of the hypothetical subnitridomolybdate “Ba 23 Na 11 (MoN 4 ) 4 ”, analogous to the reported V, Nb, and Ta compounds . NaBa was the only byphase (see powder diffraction pattern in Figure S4, Supporting Information), in accordance with the reaction equation:…”
Section: Methodsmentioning
confidence: 53%
“…It has been shown that nitridometalate anions of V, Nb and Ta in formal oxidation states +V can occur in subvalent compounds, and it is within this context we present herein the first results for new subvalent compounds containing Mo(+VI). Furthermore, we show for the first time a ReO 3 ‐like connection pattern of [Ba 6 N] units.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation